2018
DOI: 10.3174/ajnr.a5889
|View full text |Cite
|
Sign up to set email alerts
|

Automated ASPECTS on Noncontrast CT Scans in Patients with Acute Ischemic Stroke Using Machine Learning

Abstract: BACKGROUND AND PURPOSE: Alberta Stroke Program Early CT Score (ASPECTS) was devised as a systematic method to assess the extent of early ischemic change on noncontrast CT (NCCT) in patients with acute ischemic stroke (AIS). Our aim was to automate ASPECTS to objectively score NCCT of AIS patients. MATERIALS AND METHODS: We collected NCCT images with a 5-mm thickness of 257 patients with acute ischemic stroke (Ͻ8 hours from onset to scans) followed by a diffusion-weighted imaging acquisition within 1 hour. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 26 publications
5
67
1
4
Order By: Relevance
“…4 With the introduction of software packages trained on deep learning algorithms, attempts have been made to use automated ASPECTS as a way to address variability associated with human interpretation with some success. [10][11][12][23][24][25] In this study, we showed that automated ASPECTS has a similar diagnostic performance to consensus reading of experienced neuroradiologists with excellent agreement (k = 0.84). In a recent study by Maegerlein et al 11 using a different software package, similar results were shown with substantial agreement (k = 0.9) between automated and consensus reads.…”
Section: Discussionsupporting
confidence: 53%
“…4 With the introduction of software packages trained on deep learning algorithms, attempts have been made to use automated ASPECTS as a way to address variability associated with human interpretation with some success. [10][11][12][23][24][25] In this study, we showed that automated ASPECTS has a similar diagnostic performance to consensus reading of experienced neuroradiologists with excellent agreement (k = 0.84). In a recent study by Maegerlein et al 11 using a different software package, similar results were shown with substantial agreement (k = 0.9) between automated and consensus reads.…”
Section: Discussionsupporting
confidence: 53%
“…The majority of current studies describe AI-mediated detection of core stroke lesion volume on CT and MRI scans, and some use these features to predict acute stroke growth 16–19. For non-contrast CT analysis specifically, automated ASPECTS from ML used in conjunction with clinical presentation accurately associates NIHSS score and can be used to select patients for ET 20 21.…”
Section: Resultsmentioning
confidence: 99%
“…The dice obtained by this model is 75.24%, significantly lower ( P < 0.01) than 79.42% reported by the proposed method in this study, which suggests the effectiveness of this feature. In order to assess the sensitivity and stability of the lesion occurrence probability feature, we calculated the proportion of the infarcted ASPECTS regions in both 30 training images and all 100 images. It was found that the proportions of ASPECTS regions with infarction in 30 training images are similar to the ones in all 100 images.…”
Section: Resultsmentioning
confidence: 99%
“…4 Ischemic stroke lesions were segmented based on texture features and classification. 5,6 Nowinski et al detected, localized, and quantified the stroke infarct by analyzing hemisphere attenuation value distributions using percentile difference ratios. 7 Tyan et al proposed an ischemic stroke detection system including contrast enhancement, the brain tissue image area extraction, and an unsupervised region growing algorithm, and tested this method on 90 CT scan slices from 26 ischemic stroke patients.…”
Section: Introductionmentioning
confidence: 99%